The Relationship between Service Quality and Patient Satisfaction of Health Social Security Administration Agency Users in Hospital Hajj Makassar - Erlina HB; Muhajrin Muhajrin; Andi Mu’tiah Sari; Asmiana Saputri Ilyas (International Journal Of Health Science, 2025)
Healthcare services are one of the fundamental aspects of improving public welfare. In Indonesia's healthcare system, the Social Security Administration Agency (BPJS Health) plays a crucial role in ensuring equal access to healthcare services for all citizens through the National Health Insurance (JKN) program. This study aims to analyze the relationship between service quality and patient satisfaction among BPJS Health users at RSUD Haji Makassar. This research employs a quantitative method with a survey approach, where data were collected using questionnaires distributed to BPJS Health patients receiving treatment at RSUD Haji Makassar. A total sample of 118 respondents was determined using the proportionate stratified random sampling technique. Data analysis was conducted using simple linear regression tests through SPSS 23 software. The results indicate a positive and significant relationship between service quality and patient satisfaction, with a regression coefficient value of 0.471. This finding suggests that the better the service quality provided by the hospital, the higher the level of patient satisfaction. Additionally, the coefficient of determination (R²) value of 36.5% indicates that service quality contributes to patient satisfaction, while the remaining percentage is influenced by other factors not examined in this study. Based on these findings, it is recommended that RSUD Haji Makassar improve service timeliness, enhance the BPJS administration system, and strengthen the quality of interaction between medical personnel and patients.